(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
Acts of terrorism constitute one of the most serious violations of human rights and fundamental freedoms on which the European Union (EU) is founded. The threat from terrorism has grown rapidly in recent years after numerous terrorist attacks that occurred Europe lately. Taking into account the evolution of terrorist threats and too narrow legal framework EU on combating terrorism, EU decided to extend it by prescribing new terrorist offenses. Accordingly, EU adopted Directive 2017/541 on combating terrorism in 2017 by prescribing new rules in order to strengthen legal framework to prevent terrorist attacks. This is precisely the main reason why the first part of the paper covers the new EU concept of terrorist offenses. Special attention is dedicating to offenses related to terrorist activities. Furthermore, the author points out to the national legislative framework in order to examine whether the Criminal Code of the Republic of Serbia is in compliance with adopted EU framework on combating terrorism. Since terrorist attacks cause serious consequences on the population, the Directive 2017/541 complements the current legislation on the rights of victims of terrorism by imposing special provisions on its protection and support. For that reason, the second part of the article presents the scope of the rights of the victims of terrorism. In concluding remarks, the author highlights that, by adopting the Directive 2017/541, EU has developed a comprehensive criminal law response on preventing and combating terrorism. It also points out that criminal legislation of the Republic of Serbia, when it comes to the matter of combating terrorism, with certain exceptions, is already adjusted to EU framework. Finally, some recommendations for accelerating the implementation of adopted measures on combating terrorism are listed.